Evaluation of Novel Approaches to Software Engineering 7th International Conference, ENASE 2012, Warsaw, Poland, June 29-30, 2012, Revised Selected Papers - Maciaszek, Leszek A.; Filipe, Joaquim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed proceedings of the 7th International Conference on Evaluation of Novel Approaches to Software Engineering, ENASE 2012, held in Wroclaw, Poland, in June 2012. The 11 full papers presented were carefully reviewed and selected from 54 submissions. The papers cover various topics in software engineering and focus on the comparison of novel approaches with established traditional practices and by evaluating them against software quality criteria.
Keywords: Computer science; Software engineering; Logic design; Information Systems; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems